A Comparative Study of the Effect of Local and General Fatigue on Sense of Force in Healthy Young Men - Minoo Khalkhali; Mostafa Bazrafkan; Khosro Khademi Kalantari; Asghar Rezasoltani (Shahid Beheshti University of Medical Sciences, 2012)
Background and Aim: Fatigue has been proposed as one of underlying causes of musculo-skeletal injuries. Proprioceptive impairment seems to be one of the causes for this phenomenon. Few studies have investigated the effect of local fatigue on sense of force, but the effect of general fatigue on sense of force have not been studied yet. The objective of this study is to investigate the effects of local and general fatigue on sense of force and their comparison in healthy young men.Material & Methods: this Quasi-Experimental study by cross over design was conducted on 20 healthy young men recruited by simple convenient sampling from 20-40 years old staffs in national Iranian oil company. The force sense error was measured and compared in elbow extensor muscles in sitting position by force sensor before and after local and general fatigue.Results: the force sense error of extensor muscles increased after local and general fatigue without any difference between the types of fatigue. The subjects made more force than what was required.Conclusion: local and general fatigue both increases the sense of effort and it seems that the subjects match the perceived effort thus they match more force than what is required. Therefore prevention of fatigue should be considered in exercise programming for athletes. Also it is necessary to design the exercise protocols for improvement of sense of force in these subjects.